Single cell protein as an occupational hazard. Issue 2 (May 1983) - Ekenvall, L; Dölling, B; Göthe, C J; Ebbinghaus, L; von Stedingk, L V; Wasserman, J
Abstract : Single cell protein (SCP) intended for animal feed purposes was produced in a pilot plant. The SCP consisted of Methylomonas methanolica, a pseudomonas species which is an obligate methanol user. The SCP was cultured in fermenters and later dewatered and dried in a spray-drier. Seven of eight research workers had febrile reactions 6-12 hours after exposure to SCP dust. All workers had high titres of IgG and IgM antibodies against the pseudomonas species as measured with indirect ELISA and passive haemagglutination techniques. The mechanism behind the febrile reaction is judged to be a non-immunological reaction caused by endotoxins. By increasing the particle size of the SCP through using different drying procedures, a product which generated less dust was obtained.